PERAN MODAL SOSIAL DALAM KINERJA LEMBAGA KEUANGAN MIKRO: STUDI KASUS DI KOPERASI MAJU, JAKARTA - Banguning Asgha (Universitas Agung Podomoro, 2017)
The objectives of this study are to give an overview about programs implementation in a cooperative named Koperasi Maju, to identify social capital which is generated from the programs, and to find out social capital`s role in cooperative performance. Data were collected during interview towards member and staff of cooperative. Data were analysed using qualitative descriptive approach. The result shows that cooperative programs that were implemented created social capitals such as social relations in the form of interaction and trust, embedded resources in term of competence and financial access, and collective action. These social capitals also play an important role in establishing a good organization and member performance in economic and social aspects.